Increase Suicidal Mortality Rate Among Females in District Peshawar - Farooq Ahmed Abro; Rizwan Zafar Ansari; Muhammad Yousaf; Riaz Gul; Anwar UI Haq; Zahid Hussain Khalil (Gandhara University, 2018)
OBJECTIVE: To study increased suicidal mortality rate among females in district Peshawar. METHODOLOGY: The bodies of women in the reproductive age who died because of fatal deliberate self-harming were examined at Forensic Medicine Department Khyber Medical College, Peshawar from January 2015 to September 2015. RESULTS: Forty-four bodies of females were autopsied. 13 (30%) were adolescents between the age of 10-18 years. 31 (70.4%) were aged between 19-48 years. 33 of the victims committed suicide due to health-related issues. 28 (64%) victims used poisons. In almost all cases (n=38) the incident happened when the victim was alone in house or left unattended. 30 (68%) victims were brought to hospitals for treatment. 13 were found to have recurrent attempt of self-harming. CONCLUSION: Females have increased tendency to commit suicide than males especially in their reproductive age. Low socioeconomic status, cultural norms, unwanted pregnancies and ill health are the major causes.